Pengaruh suplementasi taburia (sprinkle) terhadap kadar hemoglobin balita gizi kurang usia 3-5 tahun di Kecamatan Lewimunding Kabupaten Majalengka - Budiana, Teguh Akbar; Kartasurya, Martha Irene; Judiono, Judiono (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background: Anemia is the most common nutritional problem found in the world, whichal sooccurred in under five children. Anemia is one of themain nutritional problems in Indonesia. Anemia treatment by iron (Fe) supplementation the community level were not successfull yet. This research aimed to investigate the effect of sprinkle supplementation on hemoglobin level of malnourished children aged 3-5 years.Method: Randomized pretest - posttest control group design was implemented on 66 anemic malnourished children aged 3-5 years. Study was conducted in Lewimunding subdistrict. Subjects were divided into two groups, treatment and control groups. Sprinkle supplementation and nurition education were given to treatment group for 2 months, while control group were only recieved nutrition education. All subjects treated by 400 mg Albendazol before supplementation. Data were nutrient intake collected by 24 hour Recall method. Hb was measured by Cyamethaemoglobin. Data were analyzed by Mann-Whitney,  Independent Sample Test, Wilcoxon Signed Ranks, Paired Test and linear regression method.Result: There was no difference in energy, protein, iron, vitamin B6, vitamin B12 and vitamin C on both treatment and control groups. There is no difference in hemoglobin levels between the groups before supplementation (p=0.290). Hemoglobin increased on treatment group from (11.14±0.85 mg/dl) to (12.31±0.55 mg/dl) with p=0.001. Hemoglobin also increased from (10,95 ± 0,71 mg/dl) to (11,81 ±0,53 mg/dl) in the control group (p=0.001). Sprinkle  supplementation increased by hemoglobin level  0.69 mg/dl higher than the control group (p=0.001). Multivariate analysis that hemoglobin level increased by  0.66 mg/dl higher compared to the control group after controlled by initial hemoglobin.Conclusion: Sprinkle supplementation for two months increase hemoglobin level of anemic malnourished children.